The Effect of Abstract Self-Competition on Learning Some Technical Movements on the Balance Beam in Gymnastics for Female Students - Issa, L.Dr. Ali Abdullah; Ibrahim, Prof.Dr. Zainab Sabah; Hussein, Kak Mustafa Ali (Sulaimani Journal for Humanities, 2025)
The importance of this research lies in raising the level of proper education and motivating learners to perform the most difficult movements on the balance beam. This is achieved through the use of the appropriate educational method, abstract self-competition, as this method has achieved success and progress in various sports. The research problem was: Learning on the balance beam, which is considered one of the most difficult devices, requires a method that motivates learners to perform correctly. Therefore, failure to use the optimal method will increase the difficulty of learning. Therefore, this problem requires the use of an appropriate educational method. The best method for motivation is abstract self-competition, which encourages the performance through competition and helps the learner exert effort in applying previously unsuccessful movements until they master them and perform correctly. The main objectives of the research were to identify the effect of the abstract self-competition method on teaching some artistic movements on the balance beam in gymnastics for female students. Based on these, the conclusions were: The abstract self-competition method achieved the educational objectives in teaching some artistic movements on the balance beam in gymnastics for female students. Recommendations were: Adopting the abstract self-competition method because it achieved the educational objectives in teaching some artistic movements on the balance beam in gymnastics for female students.
Keywords: Abstract selfcompetition style; learning; artistic movements; balance beam